Development of Electronic Book (ebook) based on Higher Order Thinking Skills (HOTs) for Learning Tathbiq Nahwi Ibtida'i in Higher Education - Moh. Fauzan; Muhammad Alfan; Hanik Mahliatussikah; Moch Wahib Dariyadi (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This study aimed to develop an Electronic Book (Ebook) based on Higher Order Thinking Skills (HOTS) for the Tatbiq Nahwi Ibtida'i course and test its validity. The research method used is research and development (Research and Development); there are five steps in development, namely: (1) analysis, (2) design, (3) development, (4) evaluation, and (5) revision. This ebook product was tested on ten Department of Arabic Literature, the State University of Malang students taking the course—data collection techniques through interviews and observation. Data analysis techniques include data identification, grouping, presentation and explanation of data content, and conclusions. The data analysis technique used in quantitative data is percentage data analysis. The resulting development product is an Electronic Book (Ebook) based on Higher Order Thinking Skills (HOTS) for the Tatbiq Nahwi Ibtida'i course and the validity of the resulting product. The results of this product validation, namely: the percentage of reality from media experts is 96.7%. At the same time, the value of the material expert percentage validity is 98.5%. From the field test results, the correspondent's percentage value is 83.5%; this shows that the ebook is very valid.